2022
DOI: 10.3389/fendo.2022.721569
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Transcriptional Pattern Related to Immune Cell Infiltration With Gene Co-Expression Network in Papillary Thyroid Cancer

Abstract: BackgroundA growing body of evidence suggests that immune cell infiltration in cancer is closely related to clinical outcomes. However, there is still a lack of research on papillary thyroid cancer (PTC).MethodsBased on single-sample gene set enrichment analysis (SSGSEA) algorithm and weighted gene co-expression network analysis (WGCNA) tool, the infiltration level of immune cell and key modules and genes associated with the level of immune cell infiltration were identified using PTC gene expression data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…[18] The infiltrating score of 16 immune cells and the activity of 13 immune-related pathways were performed by the “single-sample gene set enrichment analysis” function in “gsva” R package. [19]…”
Section: Methodsmentioning
confidence: 99%
“…[18] The infiltrating score of 16 immune cells and the activity of 13 immune-related pathways were performed by the “single-sample gene set enrichment analysis” function in “gsva” R package. [19]…”
Section: Methodsmentioning
confidence: 99%
“…[16] The "single-sample gene set enrichment analysis (ssGSEA)" was performed to analyzed infiltrating score of 16 immune cells and activity of 13 immune-related functions between stable group and rupture group. [17] 2.9. Drug analysis DGIdb (https://dgidb.genome.wustl.edu/) is an open-source project that offers user-friendly browsing, searching, and filtering of information on drug-gene interactions and the druggable genome.…”
Section: Immune Infiltration Analysismentioning
confidence: 99%
“…Additionally, previous studies have shown a strong positive association between improved clinical outcomes across various types of tumors and higher levels of tumor‐infiltrating NK cells 12,13 . Although the molecular properties of NK cells in malignant tumors and infectious disorders have been studied, the association between NK cells and the prognosis of THCA patients remains unclear 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…12,13 Although the molecular properties of NK cells in malignant tumors and infectious disorders have been studied, the association between NK cells and the prognosis of THCA patients remains unclear. 14,15 With the development of bioinformatics, biomarkers have been defined in various ways. On the basis of RNA-seq expression profiles, there is significant evidence that analyzing the characteristics of infiltrating immune cells could be valuable in predicting the prognosis and response to immunotherapy in patients with malignant tumors.…”
mentioning
confidence: 99%